2014
DOI: 10.1039/c4cp04161e
|View full text |Cite
|
Sign up to set email alerts
|

Achieving balanced intermixed and pure crystalline phases in PDI-based non-fullerene organic solar cells via selective solvent additives

Abstract: Herein, balanced intermixed and pure crystalline phases in N,N'-bis(1-ethylpropyl)-perylene-3,4,9,10-tetracarboxylic diimide (EP-PDI)-based non-fullerene organic solar cells (OSCs) were achieved via selective solvent additives (SAs). Poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]] (PTB7) and 7,7'-(4,4-bis(2-ethylhexyl)-4H-silolo[3,2-b:4,5-b']dithiophene-2,6-diyl)bis(6-fluoro-4-(5'-hexyl-[2,2'-bithiophen]-5-yl)benzo[c][1,2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Solvent additives often play a prominent role in optimizing donor:NFA morphologies, as NFAs can be prone to overcrystallization (for rigid planar structures) or intimate mixing (when there are fewer chemical differences between donor and acceptor). Li et al confirmed that additives can be used to address both L–L and S–L demixing processes in donor:NFA systems using PTB7:PDI and p ‐DTS(FBTTh 2 ) 2 :PDI, respectively . The greater and tunable solubility of NFAs will likely widen the selection of deposition solvents and solvent additives .…”
Section: Future Of Solvent Additive Processing In Organic Photovoltaicsmentioning
confidence: 99%
“…Solvent additives often play a prominent role in optimizing donor:NFA morphologies, as NFAs can be prone to overcrystallization (for rigid planar structures) or intimate mixing (when there are fewer chemical differences between donor and acceptor). Li et al confirmed that additives can be used to address both L–L and S–L demixing processes in donor:NFA systems using PTB7:PDI and p ‐DTS(FBTTh 2 ) 2 :PDI, respectively . The greater and tunable solubility of NFAs will likely widen the selection of deposition solvents and solvent additives .…”
Section: Future Of Solvent Additive Processing In Organic Photovoltaicsmentioning
confidence: 99%
“…The use of type II additives in the PTB7:EP‐PDI system reduces the severe aggregation of EP‐PDI molecules and increases the size of the donor:acceptor intermixed phase. These results show that a balance between the areas of the intermixed and pure phase can be achieved by selecting the solvent additive that is appropriate to the strengths of the intermolecular interactions in the donor:acceptor system …”
Section: Morphology Controlmentioning
confidence: 92%
“…For BHJ OSCs, the device performance is highly dependent on the solid-state microstructure and phase morphology of the active layer which is ideally composed of three phases: an intermixed donor/acceptor phase, a pure crystalline donor phase and a pure crystalline acceptor phases. The intermixed network promotes efficient and fast charge separation [34][35][36] whereas pure crystalline domains ensure charge transport to the electrodes. 37 Hence, indication of the mutual miscibility of the donor and the acceptor, as obtained via establishing phase diagrams is important.…”
Section: Solid-state Microstructurementioning
confidence: 99%